Expression of neurotensin receptor-1 (NTS1) in primary breast tumors, cellular distribution, and association with clinical and biological factors - Morgat, Clément; Brouste, Véronique; Chastel, Adrien; Vélasco, Valérie; Macgrogan, Gaétan; Hindié, Elif (Breast cancer research and treatment, 2021)
Purpose Neurotensin receptor-1 (NTS 1 ) is increasingly recognized as a potential target in diverse tumors including breast cancer, but factors associated with NTS 1 expression have not been fully clarified. Methods We studied NTS 1 expression using the Tissue MicroArray (TMA) of primary breast tumors from Institut Bergonié. We also studied association between NTS 1 expression and clinical, pathological, and biological parameters, as well as patient outcomes. Results Out of 1419 primary breast tumors, moderate to strong positivity for NTS 1 (≥ 10% of tumoral cells stained) was seen in 459 samples (32.4%). NTS 1 staining was cytoplasmic in 304 tumors and nuclear in 155 tumors, a distribution which appeared mutually exclusive. Cytoplasmic overexpression of NTS 1 was present in 21.5% of all breast tumors. In multivariate analysis, factors associated with cytoplasmic overexpression of NTS 1 in breast cancer samples were higher tumor grade, Ki67 ≥ 20%, and higher pT stage. Cytoplasmic NTS 1 was more frequent in tumors other than luminal A (30% versus 17.3%; p < 0.0001). Contrastingly, the main “correlates” of a nuclear location of NTS 1 were estrogen receptor (ER) positivity, low E&E (Elston and Ellis) grade, Ki67 < 20%, and lower pT stage. In NTS 1 -positive samples, cytoplasmic expression of NTS 1 was associated with shorter 10-year metastasis-free interval ( p = 0.033) compared to NTS 1 nuclear staining. Ancillary analysis showed NTS 1 expression in 73% of invaded lymph nodes from NTS 1 -positive primaries. Conclusion NTS 1 overexpression was found in about one-third of breast tumors from patients undergoing primary surgery with two distinct patterns of distribution, cytoplasmic distribution being more frequent in aggressive subtypes. These findings encourage the development of NTS 1 -targeting strategy, including radiopharmaceuticals for imaging and therapy.